Semi-transparent perovskite solar cells for tandems with silicon and CIGS1. Issue 3 (5th March 2015) - Bailie, Colin D.; Christoforo, M. Greyson; Mailoa, Jonathan P.; Bowring, Andrea R.; Unger, Eva L.; Nguyen, William H.; Burschka, Julian; Pellet, Norman; Lee, Jungwoo Z.; Grätzel, Michael; Noufi, Rommel; Buonassisi, Tonio; et al.
<x xml:space="preserve">Abstract</x> Semi-transparent perovskite solar cells with silver nanowires are stacked on CIGS and Si to achieve solid-state polycrystalline tandems with efficiency improvement.